Assessment of Pseudomonas aeruginosa Resistance to Antibiotic among Infected Patient in Hodeidah City - Al-Haddad, Mohammed Gameel; AL-Gadary, Zaid Ali; Al-Romaih, Aisha Nashwan; Al-Athwari, Safa Adel (Jocpr Publishing, 2021)
Background: All pseudomonads are widespread in nature. The most important species in this group from a medical point of view is Ps. aeruginosa, which causes infections in person with immune defects. Objective: Determine the antibiotic that are effective to Ps.aeruginosa among infected Patient in Hodeidah City , know Ps aeruginosa resistance to antibiotic among infected patient in Hodeidah City and Provide a medical information about these bacteria and resistant to antibiotic. Methods: The study was performed at microbiology department of a local Al-Hodeidah hospitals and laboratory Hodeidah city, Yemen. All the samples were collected during the study period, from May 2020 and ending in Augusta's 2020. All specimens were transported within one hours of collection to UST microbiology laboratory for processing, culture and identification. Ten isolates of Ps. aeruginosa were isolated from different clinical specimens and fully characterized by standard bacteriological procedures. Antimicrobial susceptibility pattern of each isolates was carried out by the Kirby-Bauer disk diffusion method. Results: The isolate pathogen showed highly resistant to six types of antibiotics which are Vancomycin, Ampicillin,cloxacilli, Nitrofurantion, Clindamycin, Cefoperazon, Ertapenam with a percentage of [100%], Rifampin [90%] and Trimethoprim/sulphamethoxazole [80%] while Aztreonam [70%] and Levofloxacin [50%] are considered to be sensitive. Conclusions: The result confirmed the occurrence of drug resistance strains of Ps. aeruginosa. Vancomycin, Ampicillin/cloxacilli, Nitrofurantion, Clindamycin, Cefoperazon, Ertapenam and Rifampin were found to be the most effective antimicrobial drugs. It therefore calls for a very judicious, appropriate treatment regimens selection by the physicians to limit the further spread of antimicrobial resistance Ps. aeruginosa.